2016
DOI: 10.1371/journal.pone.0167712
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Influenza and Respiratory Syncytial Viruses and the Effect of Climate Factors in Subtropical–Tropical Asia Using Influenza-Like Illness Surveillance Data, 2010 –2012

Abstract: IntroductionThe seasonality of influenza and respiratory syncytial virus (RSV) is well known, and many analyses have been conducted in temperate countries; however, this is still not well understood in tropical countries. Previous studies suggest that climate factors are involved in the seasonality of these viruses. However, the extent of the effect of each climate variable is yet to be defined.Materials and MethodsWe investigated the pattern of seasonality and the effect of climate variables on influenza and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 50 publications
3
38
1
Order By: Relevance
“…In our study, 16 (8.0 %) patients were RSV-positive and more frequently in children under 5 years old (n=15, 7.5 %). Although RSV outbreaks are known to vary from year to year according to geographical pattern, majority of RSV infection in this study was observed in March during the height of the rainy season which is consistent with earlier studies in tropical countries [24,25].…”
supporting
confidence: 92%
“…In our study, 16 (8.0 %) patients were RSV-positive and more frequently in children under 5 years old (n=15, 7.5 %). Although RSV outbreaks are known to vary from year to year according to geographical pattern, majority of RSV infection in this study was observed in March during the height of the rainy season which is consistent with earlier studies in tropical countries [24,25].…”
supporting
confidence: 92%
“…Differences in the epidemiology of influenza viruses are also evident, and outbreaks of different influenza types/ subtypes are not always synchronous. 7,17 For example, influenza A/H3N2 has been reported to cause shorter but more intense and more frequent epidemics than influenza A/H1N1 and B/Yamagata, perhaps reflecting differences in the rate of antigenic drift. 18 The stability of the currently observed pattern may also be affected by climate change, and predictions that the climates across much of Asia will become warmer and wetter may have important implications for influenza virus activity.…”
Section: Climate and Influenza In Asiamentioning
confidence: 99%
“…This reflects the range of climates, from the equatorial South to an almost polar North. 7 Recent reports that clinical protection wanes in the weeks after influenza vaccination emphasize the importance of optimally timing vaccination to local epidemiology. 8 It also raises questions as to whether influenza vaccines should be administered more frequently than annually and what may be the benefits in Asia of access to new vaccines with enhanced immunogenicity and effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Hong Kong [27] and China [28], respectively support the impact of the changing weather pattern on the magnitude of respiratory infection and the seeking of emergency healthcare. The pattern of seasonality on viral respiratory infections has clearly been reported in temperate countries, but data from tropical regions are sparse [29]. The vulnerability of children under the tropics could be emphasized by poverty-related conditions such as malnutrition and helminth infections as well as poor access to healthcare facilities.…”
Section: Introductionmentioning
confidence: 99%